P7 The epidemiology of unique ng-masts differs from that of commonly circulating ng-masts in lothian, scotland. (18th May 2015) - Mitchell, Kate; Manners, Rachel; Eastick, Kirstine; Fernando, Imali
Abstract : Background/introduction: Surveillance of gonococcal infection in Scotland has demonstrated variation in the prevalence of Neisseria gonorrhoeae multi-antigen sequence types. Some appear to circulate extensively, other sequence types (STs) may be recorded only once. Aim(s)/objectives: We aimed to review the epidemiology of gonococcal infection resulting from unique STs and examine for any association between unique STs and antibiotic resistance patterns. Methods: All gonococcal isolates from Lothian with a ST unique to Scotland, identified July 2006–October 2013, were included in the study. A control group of 76 patients infected with commonly circulating STs was also identified from the same study period. Results: 92 cases of N. gonorrhoae with unique STs were identified. Of these, 55 were truly distinct and categorised as 'unique and different'. The remaining 33 cases had STs which differed only slightly from locally circulating types and were likely to have evolved due to mutation of common strains. These were categorised as 'unique and similar'. Patients infected with 'unique and different' STs were significantly more likely than controls (p < 0.5) to have had recent sexual contact outside of Europe and/or had a recent sexual partner of non-British nationality. However, they were no more likely to have a significantly altered antibiotic resistance profile, though there was a trend towards increased antibiotic resistance. Discussion/conclusion: Gonococcal strains from non-European countries may be associated with antibiotic resistance. Identification of a 'unique and different' sequence type raises the possibility of an imported strain of gonococcal infection and demands particular vigilance in looking for antibiotic resistance.